PENERAPAN DATA MINING DENGAN METODE SINGLE MOVING AVERAGE UNTUK MENENTUKAN JUMLAH PENJUALAN OBAT - Sultan Hady; Henny Hamsinar; Reka Putri Hardiyanti (JURNAL INFORMATIKA, 2022)
Anita Farma 2 Pharmacy is one of the private pharmacies in the city of Baubau which still implements a manual system for drug sales management and has not implemented a method to predict future drug sales. So that there are various kinds of drugs that experience excess stock and some drugs experience stock shortages. The purpose of this study is to make it easier to predict future drug stock requirements at Anita Farma 2 Pharmacy using the application of data mining with the web-based Single Moving Average method. The method used in this study is the Single Moving Average (SMA) method which is a technique for calculating the average of a number from the latest actual value, updated as new values become available, carried out to forecast the following periods using the method Mean Absolute Percentage Error (MAPE) to calculate the accuracy of predictions on the Single Moving Average method. The results of the research system used the Single Moving Average method, namely period 2 (M2) of 23.25%, period 3 (M3) of 26.23% and period 4 (M4) of 28.22% using 5 drug samples with sales for 5 years from January 2017 to December 2021 Among the 3 periods of drug sales forecasting tested using manual calculations with MAPE it can be concluded that period (M2) is better than periods M3 and M4 with a percentage of MAPE "Good Forecasting" of 16.67% and the smallest error rate of 23.25 %.